2020
DOI: 10.1186/s13049-020-00766-1
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital triage performance and emergency medical services nurse’s field assessment in an unselected patient population attended to by the emergency medical services: a prospective observational study

Abstract: Background In Sweden, the rapid emergency triage and treatment system (RETTS-A) is used in the pre-hospital setting. With RETTS-A, patients triaged to the lowest level could safely be referred to a lower level of care. The national early warning score (NEWS) has also shown promising results internationally. However, a knowledge gap in optimal triage in the pre-hospital setting persists. This study aimed to evaluate RETTS-A performance, compare RETTS-A with NEWS and NEWS 2, and evaluate the emergency medical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 52 publications
(60 reference statements)
1
23
0
3
Order By: Relevance
“…These findings agree with those of Rawshani et al who concluded that EMDs without a professional medical background had a higher consumption of pre-hospital resources [ 12 ]. The reported distribution of dispatched priority varied in previous Swedish studies [ 23 , 29 , 30 ], and the current study shows the same pattern for EMD as reported recently [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings agree with those of Rawshani et al who concluded that EMDs without a professional medical background had a higher consumption of pre-hospital resources [ 12 ]. The reported distribution of dispatched priority varied in previous Swedish studies [ 23 , 29 , 30 ], and the current study shows the same pattern for EMD as reported recently [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
“…Hence, calling a dispatch decision “correct” or not is not entirely appropriate, because the true condition of the patient is not known at the time of the call. Furthermore, the performance of the reference standard, RETTS, in predicting high acuity patients as Red or Orange in the pre-hospital setting has been found as being over 80%, with a lower sensitivity in elderly, and a corresponding 64% specificity [ 26 ]. Although, as the same reference was used for both groups, it will not impact on the results.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, critically ill patients were defined according to the RETTS, which is the system that was used for risk assessment in most EDs in Sweden at the time of patient inclusion. In the prehospital setting, the system has been associated with both over- and undertriage [ 32 ]. However, among patients aged > 65 years, specificity is increasing at the expense of decreasing sensitivity [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 15 included studies, 8 were conducted in the ED (27)(28)(29)(30)(31)(32)(33)(34), and 7 in the prehospital setting (11,(35)(36)(37)(38)(39)(40). Nine studies were prospective cohort (28, 30-34, 36-38), ve were retrospective cohort (11,27,29,35,39), and one study followed a pragmatic clinical trial design (40). In the ED setting, all studies except one examined the use of MEWS (34), with two reporting on NEWS (29,34).…”
Section: Characteristics Of Articles Includedmentioning
confidence: 99%